2018
DOI: 10.1038/s41598-018-28544-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to podophyllotoxin inhibits oocyte meiosis by disturbing meiotic spindle formation

Abstract: Podophyllotoxin is used as medical cream which is widely applied to genital warts and molluscum contagiosum. Although previous study showed that podophyllotoxin had minimal toxicity, it was forbidden to use during pregnancy since it might be toxic to the embryos. In present study we used mouse as the model and tried to examine whether podophyllotoxin exposure was toxic to oocyte maturation, which further affected embryo development. Our results showed that podophyllotoxin exposure inhibited mouse oocyte matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…Successful extrusion of PB1 is the last step of oocyte nuclear maturation ( Reyes and Ross, 2016 ). Our results suggest that POD exposure significantly causes declined oocyte quality in mice, showing with a reduction of the PB1 extrusion rate, which is similar to a previous report ( Hu et al, 2018 ). During oocyte maturation, the demand for new proteins that are accomplished by proper protein synthesis, folding, modification, and trafficking is increasing ( Guzel et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Successful extrusion of PB1 is the last step of oocyte nuclear maturation ( Reyes and Ross, 2016 ). Our results suggest that POD exposure significantly causes declined oocyte quality in mice, showing with a reduction of the PB1 extrusion rate, which is similar to a previous report ( Hu et al, 2018 ). During oocyte maturation, the demand for new proteins that are accomplished by proper protein synthesis, folding, modification, and trafficking is increasing ( Guzel et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…We speculate that there are two possible causes for the aberrant distribution of organelles in oocytes: one is that POD could prevent the assembly of tubulin into microtubules, which serve as a scaffold for organelle transport and positioning ( Ardalani et al, 2017 ; Meiring et al, 2020 ); another is that the disrupted spindle structure by microtubule disassembly may affect organelle location and function since they accumulate at the spindle periphery at the MI stage, and POD exposure can disrupt the spindle formation ( Coticchio et al, 2015 ; Hu et al, 2018 ). However, the deeper explanation for the alteration of the distribution after POD exposure still needs further mechanism study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a 2018 study, weight loss and other side effects were not observed when Free PT was treated in mice xenografts to assess antitumor activity [21]. In previous reports, PT, a natural phytochemical compound, has been showed to inhibit cancers, including cervical carcinoma, breast, and prostate cancers [22,23]. Although the anti-neoplastic efficacy of PT against numerous cancers has been reported [2], its efficacy and precise pharmacological mechanisms in ESCC were not reported until now.…”
Section: Discussionmentioning
confidence: 99%
“…Podophyllotoxin (POD) is a well characterized lignan, derivatives of which are widely used in clinical treatment due to their strong antitumor and antivirus activities ( Ardalani et al, 2017 ; Zálešák et al, 2019 ). Exposure to POD can inhibit microtubule dynamics and lead to abnormal meiotic spindle formation, which influences oocyte development and maturation ( Hu et al, 2018 ; Jiang et al, 2020 ). A research article in this Research Topic by Lu et al illustrated that exposure to POD might disrupt protein synthesis, transport, degradation, and ATP production through its effects on the distribution and functions of organelles during mouse oocyte meiotic maturation.…”
Section: Introductionmentioning
confidence: 99%